The Role of miRNA in Non-Small Cell Lung Carcinoma - Ahmad Arfan; Sita Laksmi Andarini (Indonesian Society of Respirology (ISR), 2022)
Micro Ribonucleic Acids, or miRNAs, are short non-coding RNAs. Their length, on average, is 22 nucleotides, and they function in post-transcriptional regulation of gene expression. MiRNAs have their own nomenclature, and the same miRNAs can be found across different species. MiRNAs play important roles in many physiological and pathological processes in the human body. Regarding cancer, miRNAs are involved in carcinogenesis. MiRNAs work by binding completely or incompletely with messenger RNAs (mRNAs). Complete binding with mRNA produces mRNA degradation, while incomplete binding produces translational inhibition. Eventually, miRNAs decreased gene expression. In cancer, miRNAs show unique and different expression profiles. Based on their role in activating or deactivating intracellular signaling pathways, miRNAs can be classified as oncomiR or tumor suppressor miRNA. In non-small cell lung cancer (NSCLC), miRNAs are associated with gene mutation status, and they have important roles as diagnostic, prognostic, and predictive biomarkers.